2013
DOI: 10.4049/jimmunol.1203396
|View full text |Cite
|
Sign up to set email alerts
|

The Survival of Memory CD8 T Cells That Is Mediated by IL-15 Correlates with Sustained Protection Against Malaria

Abstract: Ag-specific memory T cell responses elicited by infections or vaccinations are inextricably linked to long-lasting protective immunity. Studies of protective immunity amongst residents of malaria endemic areas indicate that memory responses to Plasmodia antigens are not adequately developed or maintained, as persons who survive episodes of childhood malaria are still vulnerable to either persistent or intermittent malaria infections. In contrast, multiple exposures to radiation-attenuated Plasmodia sporozoites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 73 publications
2
31
0
Order By: Relevance
“…We cannot, therefore, determine a correlation between the numbers of CD8 In transgenic mouse models or severe combined immunodeficiency models of alloreactivity, it has been previously suggested that IL-7 and IL-15 favors the generation of central-memory and "T-memory stem cells." 26,[28][29][30] We found that IL-7 and IL-15 can also significantly enrich for the CD8…”
Section: Ccr7mentioning
confidence: 76%
“…We cannot, therefore, determine a correlation between the numbers of CD8 In transgenic mouse models or severe combined immunodeficiency models of alloreactivity, it has been previously suggested that IL-7 and IL-15 favors the generation of central-memory and "T-memory stem cells." 26,[28][29][30] We found that IL-7 and IL-15 can also significantly enrich for the CD8…”
Section: Ccr7mentioning
confidence: 76%
“…Rodent malaria models suggest that CD8+ effector memory T cells play a central role in the elimination of Plasmodium infected hepatocytes from the liver [101-104]. Immunization with attenuated sporozoites generates a reservoir of hepatic CD8+ T cells, which is maintained by KC and DC derived IL-15 in the presence of a depot of parasite LS antigens, and that resident CD44 hi CD45RB hi CD122 hi CD62L lo/hi CD8+ central memory T cells are required for the proliferation of IFN-γ producing CD44 hi CD45RB lo CD122 lo CD62L lo effector memory T (T EM ) cells capable of conferring protection against reinfection [104-107]. In vitro studies have shown that P. berghei and P. yoelii specific CD8+ T cells are capable of contact-dependent recognition of parasite antigen on the surface of infected hepatocytes and elimination of LS in the absence of cytokines such as IFN-γ or TNF-α [108-110].…”
Section: Imaging the Elusive Plasmodium Liver Stagementioning
confidence: 99%
“…While CD8 + T EM cells are the main producers of IFN-γ, CD8 + T CM cells form a reservoir of Ag-specific cells needed for the maintenance of long-term protective immunity [40]. We asked whether immunization of TAP −/− mice with P. berghei RAS would also induce differentiation of liver CD8 + T cells.…”
Section: Plasmodium Berghei Ras Derived Ags Induce An Expansion and Dmentioning
confidence: 99%